Implementasi Administrasi dan Manajemen Peserta Didik di MIN 1 Lhokseumawe: Model Pengelolaan Berbasis Karakter dan Inklusivitas - Aqsha, Rauzatul; Zahara, Nurfitah (Pascasarjana IAIN Lhokseumawe, 2025)
This study examines the implementation of student administration and management at MIN 1 Lhokseumawe, aiming to formulate a character-based and inclusive management model within Islamic education. Administration operates at the policy and strategic planning level, including the formulation of regulations, record-keeping, and oversight of student-related policies. Meanwhile, management focuses on operational implementation, such as student admission (PPDB), character development, counseling services, and personal growth activities. This research employed a qualitative approach with a case study design, using interviews, observations, and document analysis. Data were analyzed following the Miles et al. model through data condensation, display, and conclusion drawing, with triangulation of sources and methods to ensure validity. The findings reveal that the integration of administration and management at the madrasah is realized using the EMIS system, regular evaluative meetings, and collaborative leadership between teachers and school administrators. The application of Islamic values such as syūrā (consultation), amānah (trustworthiness), and iḥsān (excellence) serves as the moral foundation of the entire management process. The resulting model can be categorized as collaborative and data-driven management, integrating administrative policy direction with adaptive and reflective managerial practices. This synergy creates an accountable, participatory, and character-oriented student management system aligned with the spirit of modern Islamic education.